Self referent processing in perceptions of verbal and visual commercial information - Debevec, Kathleen; Romeo, Jean B. (Lawrence Erlbaum Associates, Inc., 1992)
We examined how visual information in an ad may interact with and influence processing of verbal information and facilitate or inhibit self-referent judgments. Self-referencing is viewed as a mediator between individuals' perceptions of verbal and visual stimuli in advertising and their subsequent attitudes and intentions. A 3 × 2 experimental design was used to examine the effects of three verbal copy strategies (self copy, product benefit copy, and typical user copy) and two visual image strategies (product featured or typical users featured). To enhance realism, the study was conducted in the context of testing a new experimental magazine. The verbal focus of an ad was shown to encourage varying levels of self-referencing and differential attitudes and intentions when a product visual was featured, but not when a slice-of-life setting was featured. Self copy (copy written in the second person vernacular) accompanied by the product visual was the most effective strategy in encouraging self-referencing and favorable attitudes and intentions.